Intercalation chemistry of the novel layered double hydroxides [MAl4(OH)(12)](NO3)(2)center dot gamma H2O (M = Zn, Cu, Ni and Co). 1: New organic intercalates and reaction mechanisms - Williams, G; Dunbar, T; Beer, A; Fogg, A; O'Hare, D (2006)
The intercalation chemistry of a recently synthesized family of layered double hydroxides, [MAl4(OH)12](NO3) 2·yH2O (M = Zn, Cu, Ni, Co), has been explored. A range of dicarboxylates, mono- and disulfonates have been intercalated successfully, and the resulting materials fully characterised. The interlayer spacing of the dicarboxylates is found not to vary linearly with the length of the carboxylate chain, but instead the acid species are arranged so that the ends of the dicarboxylate chains point directly at the localized metal atoms in the layers. In situ diffraction experiments have been performed to investigate the kinetics and mechanisms of the intercalation processes. The dicarboxylates are found to intercalate very quickly, with the reactions being complete within a few minutes at room temperature. In contrast, the sulfonates intercalate more slowly, and quantitative kinetic parameters may be measured for these reactions. All the reactions were found to be direct one-step transformations. The sulfonate intercalation processes are proposed to be nucleation controlled in the vast majority of cases for the M = Zn, Cu and Co materials, with the rate limiting step being the expansion of the interlayer space to accommodate the relatively large organic guest anions. In contrast, the reactions of the M = Ni LDH are found to be purely diffusion controlled: as soon as the guest reaches the host particles, it intercalates.